High‐Capacity Layered‐Spinel Cathodes for Li‐Ion Batteries. Issue 17 (17th August 2016) - Nayak, Prasant Kumar; Levi, Elena; Grinblat, Judith; Levi, Mikhael; Markovsky, Boris; Munichandraiah, N.; Sun, Yang Kook; Aurbach, Doron
Abstract: Li and Mn‐rich layered oxides with the general structure x Li2 MnO3 ⋅(1– x ) LiMO2 (M=Ni, Mn, Co) are promising cathode materials for Li‐ion batteries because of their high specific capacity, which may be greater than 250 mA h g −1 . However, these materials suffer from high first‐cycle irreversible capacity, gradual capacity fading, limited rate capability and discharge voltage decay upon cycling, which prevent their commercialization. The decrease in average discharge voltage is a major issue, which is ascribed to a structural layered‐to‐spinel transformation upon cycling of these oxide cathodes in wide potential ranges with an upper limit higher than 4.5 V and a lower limit below 3 V versus Li. By using four elements systems (Li, Mn, Ni, O) with appropriate stoichiometry, it is possible to prepare high capacity composite cathode materials that contain LiMn1.5 Ni0.5 O4 and Li x Mn y Ni z O2 components. The Li and Mn‐rich layered‐spinel cathode materials studied herein exhibit a high specific capacity (≥200 mA h g −1 ) with good capacity retention upon cycling in a wide potential domain (2.4–4.9 V). The effect of constituent phases on their electrochemical performance, such as specific capacity, cycling stability, average discharge voltage, and rate capability, are explored here. This family of materials can provide high specific capacity, high rate capability, and promising cycle life. Using Co‐free cathode materials is also an obvious advantage of these systems. Abstract : Cathodes in phase : Li and Mn‐rich layered‐spinel materials x Li[Li1/3 Mn2/3 ]O2 ⋅(1– x ) LiNi0.5 Mn1.5 O4 ( x =0.3, 0.6) synthesized by the self‐combustion reaction and used as cathodes in Li cells exhibit capacities ≥200 mAh g −1 . The cathodes demonstrate excellent cycling stability, indicating promising application in Li‐ion batteries. The effect of constituent phases on the electrochemical performance of the cathodes is also explored.